KUALITAS KIMIA DAN FISIK DAGING AYAM (KUB) YANG DIBERI RANSUM KOMERSIAL DISUBTITUSI LIMBAH ROTI - N. L. P, SRIYANI; SITI, N. W.; ARIANA, I. N. T.; MIWADA, I. N. S. (Majalah Ilmiah Peternakan, 2024)
The objective of this study is to assess the chemical and physical quality of meat from Kampung Unggul Balitbangtan (KUB) chickens when they are fed with bread waste. The research utilized a Completely Randomized Design (CRD) comprising 3 treatments and 5 replications, with each replication containing 2 KUB chickens. The three treatments were as follows: (P0) KUB chickens fed a 100% commercial ration, (P1) KUB chickens fed a mixture of 75% commercial ration and 25% bread waste, and (P2) KUB chickens fed a mixture of 50% commercial ration and 50% bread waste. The findings indicated that the substitution of commercial rations with bread waste at levels of 25% and 50% had a significant impact (P<0.5) on the chemical quality of meat, specifically moisture content, protein content, and fat content. In terms of the physical quality of the meat, parameters such as pH, water holding capacity, and cooking losses also showed significant differences (P<0.05). Therefore, based on the research results, it can be concluded that replacing commercial rations with bread waste at the levels of 25% and 50% leads to a decrease in both the chemical and physical quality of KUB chicken meat.